Improving the Reading Ability of Children Aged 5-6 Years Through Big Book Media at Puri Cendikia Kindergarten for the 2023/2024 Academic Year - Sinta Devi, Dwi; Hadi, Rusman (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to describe how to improve children's reading abilities at Puri Cendikia Kindergarten for the 2022/2023 school year. This research focuses more on how to improve children's reading abilities at the age of 5-6 years. This research is Classroom Action Research (PTK) where the subjects in this research are group B students from Puri Cendikia Kindergarten with a total of 8 students. The focus of this research is the reading ability of children aged 5-6 years. In this research, researchers used Big Book media to improve children's ability to read to meet the criteria desired by the researcher. In this study, data collection only used two cycles, in the first cycle the level of children's reading abilities still looked low because there were still some children's reading abilities that had not improved significantly. In cycle I with Developing As Expected (BSH) results there were 4 children or equivalent to 50%, and Very Well Developing (BSB) consisted of 1 child or equivalent to 12.5%. Apart from that, there is cycle II as a planning improvement action where from cycle I to cycle II there was an increase of 37.5% so that children who developed according to expectations (BSH) consisted of 6 children or the equivalent of 75%, and developed very well. (BSB) totaling 3 children or the equivalent of 37.5%. So with this increase, the researcher stopped his research because the researcher had obtained the correct results according to the desired classical value. However, individual scores are still not perfect and there are still children who fall below the assessment criteria.